Environmentally Friendly Roof Tiles: Comparative Study of a Mixture of Clay and Balinese Traditional Ceremonial Waste - Andre Jefri; Susilawati; Masturi (JST (Jurnal Sains dan Teknologi), 2026)
The limitations of synthetic polymer-based supercapacitor separators, which are less environmentally friendly and negatively affect performance, represent a major challenge in the development of sustainable energy storage systems. In addition, liquid waste from the tofu–tempeh industry, which has not been optimally utilized, poses a potential risk of environmental pollution. This study aims to analyze, evaluate, and optimize the utilization of nata de soya membranes as bio-based separators, as well as to examine the effect of variations in monovalent sulfate electrolytes on the structural and electrochemical performance of supercapacitors. This research employs an experimental method with a post-test only design. The research subjects consist of nata de soya membranes treated with three electrolyte variations, namely K₂SO₄, Na₂SO₄, and (NH₄)₂SO₄, each tested in three repetitions. Data were collected through structural characterization using SEM and EDX, and electrochemical performance testing using CV, EIS, and GCD with standardized laboratory instruments. Data analysis was conducted using both quantitative and qualitative approaches by comparing the performance of each electrolyte variation. The results indicate that the (NH₄)₂SO₄ electrolyte produces the highest specific capacitance and the lowest internal resistance, supported by a more porous membrane structure. It can be concluded that nata de soya has strong potential as an environmentally friendly separator with optimal performance. The implications of this study support the development of sustainable energy materials based on biomass waste.